2020
DOI: 10.31616/asj.2019.0026
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Conditioned Medium from Human Breast Milk Stem Cells in Treating Spinal Cord Injury

Abstract: Study Design: Experimental animal study.Purpose: This study investigated the therapeutic effects of human breast milk stem cell (BMSC)-conditioned medium (BMSC-CM) in a model of spinal cord injury (SCI) in male Sprague-Dawley rats.Overview of Literature: SCI is one of the leading causes of disability in addition to sensory and motor impairment. So far, there have been no successful treatments for SCI. Given the positive outcomes associated with using stem cells and their derivatives as a treatment for various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…In this study, after administering HNSCs-secretome to SCI-affected rats, there was a decrease in the pro-inflammatory cytokine TNF-α, accordance with five previous studies by Huang et al [ 23 ], Cizkova et al [ 24 ], Huang et al [ 25 ], and Borhani-Haghighi et al [ 26 ], who stated that there was a decrease in TNF-α after MSC-secretome intervention in mouse-model SCI. The cytokine TNF-α is the most influential proinflammatory mediator in SCI, followed by other proinflammatory mediators such as interferon gamma, IL-6, and IL-8[ 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, after administering HNSCs-secretome to SCI-affected rats, there was a decrease in the pro-inflammatory cytokine TNF-α, accordance with five previous studies by Huang et al [ 23 ], Cizkova et al [ 24 ], Huang et al [ 25 ], and Borhani-Haghighi et al [ 26 ], who stated that there was a decrease in TNF-α after MSC-secretome intervention in mouse-model SCI. The cytokine TNF-α is the most influential proinflammatory mediator in SCI, followed by other proinflammatory mediators such as interferon gamma, IL-6, and IL-8[ 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…To assess the locomotor expression, the BBB open-field test was performed on days 1, 3, 7, 14, 21, and 28 after injury [ 16 ]. The BBB measures the tail, body, legs, trunk stability, limb movement, and toe clearance, all of which are examined to measure the locomotor abilities [ 20 , 21 ]. The score shows a range of numbers between 0 and 21.…”
Section: Methodsmentioning
confidence: 99%
“…However, further research is required to prove this hypothesis. A recent study using breast milk stem cells to treat spinal cord injury showed that the administration of these cells reduced apoptosis and inflammation at the site of injury, indicating their influence on immune responses and therapeutic potential ( 258 ).…”
Section: The Importance Of Breast Milk For the Development Of The Neonatementioning
confidence: 99%